Apoptosis, Expression of PAX3 and P53, and Caspase Signal in Fetuses with Neural Tube Defects. Issue 19 (8th August 2017) - Wang, Linlin; Lin, Shanshan; Yi, Deqing; Huang, Yun; Wang, Caiyun; Jin, Lei; Liu, Jufen; Zhang, Yali; Ren, Aiguo
Abstract : Background: Neural tube defects (NTDs) are among the most common and severe congenital malformations of the central nervous system. Animal studies have shown that apoptosis is involved in the development of NTDs. However, little evidence is available from human studies. We aim to examine the level of apoptosis and expression of apoptosis‐regulating proteins of human terminated fetuses. Methods: A total of 37 NTD cases and 21 controls from pregnancy terminations were recruited. Tissues of the central nervous system were obtained through autopsy. Apoptosis of neuroepithelial cells was examined by terminal deoxynucleotidyl transferase–mediated deoxyuridinetriphosphate nick end‐labeling (TUNEL) assay. Expression of PAX3, p53, and caspase 3/8/9 in central nervous tissue was measured using Western blotting. Results: More TUNEL‐positive apoptosis cells were observed in the central nervous tissue of NTD cases than those of controls ( p < 0.05). In spinal cord tissue, lower PAX3 expression, higher p53 expression, and increased levels of cleaved caspase 3(17kD) and cleaved caspase 8 (18kD) were found in anencephaly cases but not in spina bifida cases when compared with controls. In brain tissue, levels of PAX3 were significantly reduced in both encephalocele and spina bifida subtypes; the expression levels of cleaved caspase 3(17 kD) of encephalocele cases and cleaved caspase 8(47/45 kD) in spina bifida cases were higher than in controls; no difference was found in the expression of p53 or caspase 9 between NTDs and controls. Conclusion: These findings provide some evidence that excessive apoptosis in fetal central nervous tissues may be associated with the development of human NTDs. Birth Defects Research 109:1596–1604, 2017. © 2017 Wiley Periodicals, Inc.